Entrepreneur Competence Measure (ECM) - electronically controlled / Rohani Mohd … [et al.] - Mohd, Rohani; Yahya, Khulida Kirana; Kamaruddin, Badrul Hisham; Abu Bakar, Nordin; Yusof, Mohd Fikri (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
ECM measures the competence level of SME owner managers in Malaysia. It is electronically controlled. Psychological aspects (values and motivation) can contribute to entrepreneurial orientation and performance. The government can plan for SMEs' training (Malays, in particular) if entrepreneurs' psychological aspects (values and motivation) are known first, not financial performance. The people who run the system need to be corrected, rather than improving system. This has a sustainable impact. A logit ruler (to be developed by Rasch Model) will measure entrepreneurial competence by referring to the psychological aspects of the entrepreneur. This creates competence classification groups (Exemplar, Competence, Mediocre or Survivor). The ruler will identify internal aspects (values, motivation and entrepreneurial orientation) that need to be focused by respective groups. Depending on your classification, you will know how critical those internal factors are to you. Training providers can prepare improvement or enrichment programs for you. As people are corrected, their socio-economic status will improve, hence creating well- balanced individual.